2021
DOI: 10.26434/chemrxiv-2021-7chqx
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Is maximising current density always the optimum strategy in electrolyser design for electrochemical CO2 conversion to chemicals?

Abstract: Electrochemical conversion of CO2 to chemicals and fuels can potentially play a role in reducing CO2 emissions from industrial processes and providing non-fossil fuel routes to important chemical feedstocks. Most of the recent research on electrocatalysts for CO2 reduction (CO2R) focuses on achieving maximum selectivity for desired products at the highest possible current density. This approach assumes that maximising current density leads to the lowest cost of CO2R (e.g. $·kg-1 CO2 converted) because it requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…We also performed a long-term stability test with the untreated Ag GDE in our other work 49 (also shown in Figure S19) and found that the selectivity of CO was only around 62%, much less than what we observed with the Ag-U-mixed GDE (85%). In addition, the electrocatalytic performance S3.…”
Section: Role Of Urea In Catalystmentioning
confidence: 73%
“…We also performed a long-term stability test with the untreated Ag GDE in our other work 49 (also shown in Figure S19) and found that the selectivity of CO was only around 62%, much less than what we observed with the Ag-U-mixed GDE (85%). In addition, the electrocatalytic performance S3.…”
Section: Role Of Urea In Catalystmentioning
confidence: 73%
“…Assumptions for the material and energy balance in the CO 2 conversion unit were based on laboratory demonstration data with additional inputs from literature sources. Briefly, the model was based on multiple two-cell vapour fed electrolyser stacks with the capacity to treat 50 tCO 2 per day; further details can be found in our other report [ 33 ]. The current density of the electrolyser was altered from 2.68 V at 0 A/m 2 to 3.59 V at 1862 A/m 2 to produce the H 2 -rich gas with different H 2 /CO compositions.…”
Section: Methodsmentioning
confidence: 99%
“…The electricity consumption for CO 2 conversion is proportional to the H 2 generation, which can be estimated as in Equation (2) [ 33 ]:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 A much larger electrode area is required to process about 50 t day −1 of CO 2 to achieve competitive cost compared to petrochemical processes. 6 Although the selectivity to desired products such as CO and C 2 H 4 and current density achieved in bench-scale experiments approach likely industrial requirements, 7 the present energy efficiency and stability of the lab electrolysers are far from the targets set by Sargent et al 8 The challenges in attaining a scalable performance primarily stem from operational stability of a gas diffusion electrode (GDE) as the cathode. The GDE not only exhibits exceptional mechanical resilience due to its exibility but, more importantly, effectively addresses the mass transport issue with planar electrodes in static electrolysers.…”
Section: Introductionmentioning
confidence: 99%